Prediksi Kecepatan Pengeboran Menggunakan Regresi LASSO pada Lapisan Interburden Batubara - Aullia Bintang Jaladri; Bagus Wiyono; Singgih Saptono; Tedy Agung Cahyadi; Hakim Erlangga Bernado Sakti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Rotary drilling operations at Pit Bendili, PT Kaltim Prima Coal, require operational parameter optimization to achieve the company’s target Rate of Penetration (ROP) of 110 m/h. Drilling speed is significantly influenced by the interaction between mechanical operational factors and rock characteristics. Pit Bendili has an average Uniaxial Compressive Strength (UCS) of 15.46 MPa, classified as weak rock, yet hardness variations between coal seams cause workload fluctuations. This study aims to model and analyze the combination of pulldown pressure (PP) and rotational pressure (RP) on the velocity of penetration (VP) to meet the ROP target. Operational parameters were modeled using the Python-based Least Absolute Shrinkage and Selection Operator (LASSO) Regression method. Analysis of 134 blast hole operational datasets yielded a Mean Absolute Percentage Error (MAPE) of 7.9%, indicating excellent predictive model accuracy. Through this LASSO model, PP and RP combinations can be precisely adjusted to ensure drilling velocity consistently meets or exceeds the 110 m/h target across various rock layers.